Seed Damage by the Neotropical Brown Stink Bug, Euschistus heros (F.) to Resistant Soybean Cultivars with the Block Technology Versus a Susceptible Cultivar. Issue 2 (10th March 2022) - Pastorio Oliveira, Weslley; Lucini, Tiago; Ricardo Panizzi, Antônio
Abstract: Laboratory and greenhouse studies were conducted with the Neotropical brown stink bug, Euschistus heros (F.), to evaluate and compare adult damage at two infestation levels (2 and 4 adults/plant) and feeding behavior on seeds of three resistant soybean cultivars bearing the Block technology ('BRS 1003 IPRO', 'BRS 543 RR', and 'BRS 391') compared to a susceptible cultivar ('BRS 5601 RR'). No difference in number or weight of damaged seeds (as percentages) was found among the cultivars at either infestation level. Differences were only observed between infestation levels within cultivar; higher values were reported with 4 adults/plant, except for 'BRS 543 RR'. At 2 adults/plant, total seed area damaged (mm 2 ) and percentage of seed area damaged were significantly lower only on 'BRS 1003 IPRO'; significant differences among cultivars were found in damage to internal but not external seed surfaces. At 4 adults/plant, all Block cultivars differed from 'BRS 5601 RR' in overall seed damage, and greater percent damage occurred on both seed surfaces on 'BRS 5601 RR'. Electropenetrography (EPG) demonstrated that adults reached and fed in the seeds of all soybean cultivars. However, the feeding event duration in seeds of Block cultivars was much shorter than on 'BRS 5601 RR', which likely explains differences between internal and external seed damage. Furthermore, the total duration of feeding activities on seeds of Block cultivars was ca. 4–6 times shorter than on the susceptible cultivar; these two EPG feeding variables account for the lower seed damage observed for the Block cultivars. These cultivars represent an important new strategy for pest control on soybean.